RNA modification m6Am: the role in cardiac biology - Benak, Daniel; Kolar, Frantisek; Zhang, Lu; Devaux, Yvan; Hlavackova, Marketa (Epigenetics, 2023)
Epitranscriptomic modifications have recently emerged into the spotlight of researchers due to their vast regulatory effects on gene expression and thereby cellular physiology and pathophysiology. N6,2'-O-dimethyladenosine (m6Am) is one of the most prevalent chemical marks on RNA and is dynamically regulated by writers (PCIF1, METTL4) and erasers (FTO). The presence or absence of m6Am in RNA affects mRNA stability, regulates transcription, and modulates pre-mRNA splicing. Nevertheless, its functions in the heart are poorly known. This review summarizes the current knowledge and gaps about m6Am modification and its regulators in cardiac biology. It also points out technical challenges and lists the currently available techniques to measure m6Am. A better understanding of epitranscriptomic modifications is needed to improve our knowledge of the molecular regulations in the heart which may lead to novel cardioprotective strategies.
Keywords: DNA Methylation; messenger RNA; biologie; heart; RNA, Messenger; Adenosine; Biology; adenosin; metylace DNA; epitranscriptomics; m6A; N6,2‘-O-dimethyladenosine; N6-methyladenosine; RNA; m6Am